Effects of daily versus weekly iron therapy in infants between 6-24 months for iron deficiency anemia - Kargarnovin, Z; Tamkins, A; Jalaly, M; Salavan, K; Pam, L (Advances in Nursing & Midwifery, 2010)
Background and aim Iron deficiency anemia is one of the main nutritional problems at different age groups particularly pregnant women and young children worldwide. The aim of this study was to compare the effects of daily with weekly iron therapy in infants between 6-24 months with iron deficiency anemia in the South of Tehran. Materials and methods In this clinical trial study, 160 anemic infants diagnosed by hemoglobin test were randomly selected and divided into 2 equal control and experimental groups. The control group was given 5ml ferrous sulfate syrup daily containing 40mg ferrous sulfate but, in the experimental group, iron was given in the same amount once a week on Friday mornings. Hemoglobin was measured at the beginning of the intervention, after 3 months and immediately after the therapy (6 months). A questionnaire, physical examination, home visit and laboratory tests were used for data collection. Data were analyzed by SPSS 11/5. Findings Both methods were effective on increasing hemoglobin level with no significant difference. Drug compliance in weekly method (77%) was significantly better than daily protocol (49%) for mothers. Conclusion Weekly administration of iron compared with daily consumption seems superior due to similar effects, better compliance of mothers and lower costs for the treatment of anemia in infants between 6 and 24 months. Keywords: Anemia, Iron deficiency, Infants, Nutrition, Ferritin, Iron supplement. *Corresponding Author: Zahra Kargarnovin, Dept. of Community Nutrition, Faculty of Nutrition Sciences and Food Technology, Shahid Beheshti University of Medical Sciences and Health Services, Tehran, Iran. Tehran, Iran. E-mail: zknovin@hotmail.com